Nuclear Plants Trends for Development Planning in Egypt - Youssef , Abeer (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
Fossil fuel combustion is blamed for global climate change and associated greenhouse gases (GHG) are the main types of pollution created by GHG emissions from combustion (i.e., CO2) and as such an ever-increasing level of CO2 emissions make GHG, their pollutants and the complications of climate change awareness more significantly urgent. There is significant concern from policymakers concerning, fuel consumption, energy security and the challenges of GHG emissions created by fossil fuel consumption has created a focus on alternative, cleaner sources of energy both from public policy analysis and political perspectives. As such, clean sources of energy (i.e., nuclear and renewable sources of energy) are being promoted as alternative sources of energy and provide effective tools for mitigating the negative impacts of climate change and are being used as part of a new energy policy strategy. There has also been much discussion among various countries with regard to the need for increasing share of energy supply from nuclear energy, thereby diversifying the energy supply chain, decreasing reliance on imported fossil fuels that may be subject to significant price volatility and improving energy security. The present work will contribute to knowledge development and interface towards improving the power generation infrastructure of nuclear energy in Egypt through a study of the relationship of nuclear energy, the economy and CO2 emissions using the experience from other developed countries.